2019
DOI: 10.2147/nss.s218402
|View full text |Cite
|
Sign up to set email alerts
|

<p>Management Of Excessive Sleepiness In Patients With Narcolepsy And OSA: Current Challenges And Future Prospects</p>

Abstract: Excessive daytime sleepiness (EDS) can be caused by insufficient sleep but is also a manifestation of medical or sleep disorders and a side effect of medications. It impacts quality of life and creates safety concerns in the home, at work, and on the roads. Screening questionnaires can be used to estimate EDS, but further evaluation is necessary. EDS is a common symptom of both narcolepsy and obstructive sleep apnea (OSA). Polysomnography and multiple sleep latency testing are used to diagnose these disorders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…Clinically, EDS overlaps with other common sleep and mood disorders that are considered causal to EDS, such as obstructive sleep apnea (OSA), narcolepsy, depression, and post acute sequelae of COVID-19 15 , with an estimated prevalence of 20% of adults in the United States 16 . These causes are usually misdiagnosed or undiagnosed in the population, even when a patient performs a sleep study 7 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, EDS overlaps with other common sleep and mood disorders that are considered causal to EDS, such as obstructive sleep apnea (OSA), narcolepsy, depression, and post acute sequelae of COVID-19 15 , with an estimated prevalence of 20% of adults in the United States 16 . These causes are usually misdiagnosed or undiagnosed in the population, even when a patient performs a sleep study 7 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…EDS appears ordinarily among individuals with sleep disorders, particularly those with OSA and NT1. 1,2,4 Although several studies have identified differences between OSA and NT1 on symptomatology and objective tests, 21,22 there is still no reliable model to predict NT1 in patients with OSA. [11][12][13] Our study indicated the comorbid NT1 could be accurately predicted by certain ML models.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs such as benzodiazepines or opioids that may cause sedation or drowsiness also should be discontinued. Beta-blockers, which can cause drowsiness and suppression of REM sleep, should be held for 2 weeks before the study if approved by the prescriber 21. Patients also complete a sleep log for 1 week before testing, to assess their routine sleep/wake schedule 19…”
Section: Diagnosismentioning
confidence: 99%